The Influence of Price Perception, Service Quality, Store Atmosphere and Word of Mouth on Purchasing Decisions - Kevin, Ainul; Simon, Zainal Zawir (SAN Scientific, 2024)
This research was conducted with the aim of examining the influence of price perceptions, service quality, store atmosphere, and word of mouth on purchasing decisions. The sample used in this research was consumers of the Kopi Kecil coffee shop in Cempaka Putih who had made a purchase and dine-in at least once at the Kopi Kecil coffee shop, totaling 100 people. The data collection method uses a questionnaire. Data analysis uses multiple linear regression analysis. The study results show that partially, price perception has an insignificant influence on purchasing decisions, service quality has an insignificant influence on purchasing decisions, partially, store atmosphere has a positive and significant influence on purchasing decisions, and partially, word of mouth has a positive influence and is significant to purchasing decisions. Managerial implications in this research Managers must understand how price influences customer perceptions, offer product packages at cheaper prices than buying them separately to increase the value perceived by customers, and Collect and analyze feedback from customers to find out areas that need to be improved in service.